Primary squamous cell carcinoma of thyroid gland with local recurrence: ultrasonographic and computed tomographic findings - Jang, Ja Yoon (Korean Society of Ultrasound in Medicine, 2014)
Primary squamous cell carcinoma of the thyroid gland (PSCCT) is a rare malignancy that presents with advanced disease and poor prognosis. It is difficult to diagnose PSCCT in its early stage because of its rarity and lack of typical imaging findings. We experienced an elderly woman with PSCCT confirmed by surgery. Although preoperative fine-needle aspiration revealed no malignancy, surgical resection was performed because the ultrasonogram showed diffuse microcalcifications, which suggested malignancy, and clinically, the mass grew rapidly to compress the trachea. Local tumor recurrence was noted at 3 months after surgery. Surgical resection or repeat biopsy should be considered if a cytologically benign thyroid mass shows imaging or clinical features of malignancy.